Nucleoporin 107, 62 and 153 mediate Kcnq1ot1 imprinted domain regulation in extraembryonic endoderm stem cells - Saqib S. Sachani (Nature Portfolio, 2018)
Genomic imprinting restricts transcription to predominantly one parental allele. Here the authors perform a screen for epigenetic factors involved in paternal allelic silencing at the Kcnq1ot1 imprinted domain in mouse extraembryonic endoderm stem cells and characterize a role for specific nucleoporins in mediating Kcnq1ot1 imprinted regulation.